Особливості розподілу катіонів у п’ятишаровій перовскітоподібній структурі сполук та фаз типу AnBnO3n+2 - Тітов, Ю.О.; Бєлявіна, Н.М.; Марків, В.Я.; Слободяник, М.С.; Чумак, В.В.; Ящук, В.П. (Видавничий дім "Академперіодика" НАН України, 2008)
The crystal layer perovskite-like structures (LPS) of five-slab phases Ca5−xSrxTiNb4O17 (x = 1, 2, 3, 4) have been determined by X-ray powder diffraction. The peculiarities of LPS of synthesized phases and the known five-slab compounds of the A5BIBII 4 O17 type have been analyzed and the regularities of the distribution of B-type cations in the five-slab perovskite-like structure of compounds and phases of the A5BIBII 4 O17 type have been determined.